DAMPAK KETERAMPILAN DASAR MENGAJAR GURU EKONOMI AKUNTANSI TERHADAP MOTIVASI BELAJAR SISWA SMK DI KOTA PEKANBARU - Rina Selva Johan; Hendripides ' (Program Studi Pendidikan Ekonomi Universitas Riau, 2016)
The basic skills in teaching is a very important component because a teacher willknow the condition of their students and do actions that can make students moreenthusiasm in learning. The purpose of this research was determine impact thebasic skills of Economic-Accounting’s teacher for student’s motivation and howmuch impact the basic skills of Economic-Accounting teachers to vocationalstudent’s motivation in Pekanbaru city. The benefits of this research is to improvethe quality of learning for teachers and increase learning motivation for students.The population of this study is all teachers of Economic-AccountingTeachers ofVocational School in the Pekanbaru city, which consists of 54 teachers. The maininstruments used to collect data was a questionnaire, then the data were analyzedusing percentage formula, to determine whether there is the impact of basic skillsteaching to student’s motivation from used Chi Square approach. The resultsshowed a 57% (31 respondents) of respondents have good basic skills teaching.While 52% (28 students) have a good motivation to learn. Basic skills in teach havean impact to studentss motivation. This is evidenced by the results of statistical teststhat the t-test (4.905) > t-table (0.360).Key words: Teaching Basic Skills, Motivation